A Middle Cuneiform Stress Fracture in an Adolescent Athlete: A Case Report and Literature Review. Issue 12 (October 2019) - Krebs, Paul; Borchers, James
A 13-year-old female soccer and basketball athlete presented with pain in the arch of her foot. Magnetic resonance imaging confirmed the diagnosis of a middle cuneiform stress fracture. The patient's stress fracture healed nonoperatively over a 10-week period complicated by nonadherence to a fracture boot, after which she was progressed back to full activity. Knowledge of these fractures and their treatment are important for sports medicine physicians, as they can often be overlooked, given their infrequent occurrence. There have been 8 previous case reports and 1 case series on cuneiform stress fractures, and these are summarized with this case report.